PERANCANGAN APLIKASI E-TRAVEL BERBASIS WEB - Kautsar, Sandy (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2019)
E-travel is a way to book a trip or tarvel through electonic media. This application uses the PHP programming language, in this application also uses the RUP method in which there are four stages starting inception, elaboration, construction and the last there is a transition while doing this research also researchers conducted data retriveal which uses interviews and literatur studies. The result of the research succeeded in accordance with the expectaions and objectives of the study were to facilitate travel.